Anxiety and Depression: a reflection on the impacts of the pandemic on the lives of Brazilians (Research, Society and Development, 2022)
The present study aims to investigate the reflexes of the COVID-19 Pandemic on people's lives, the consequences of the challenges of social isolation and what preventive measures were taken to alleviate the problems that were generated as a result of this isolation. Thus, it was necessary to improve knowledge about aspects of the participants' daily experience and activities and their own understanding and reflections on their well-being. As well as presenting ways to deal with the phenomenon within the World context. The research is Quantitative - Analysis of items related to the impact of social isolation on the lives of Brazilians. A survey was carried out with the application of questionnaires, answered electronically, by the Google Docs.® system, with closed multiple-choice questions or with response options in the Likert scale format. The results showed that social isolation significantly impacted the lives of individuals, causing psychological and physical consequences such as anxiety and depression.